ANALISIS DAMPAK TRANSPARANSI DAN AKUNTABILITAS TERHADAP KUALITAS TATA KELOLA KEUANGAN DI KEMENTERIAN AGAMA SUMATERA UTARA: STUDI KEPUSTAKAAN - Muhammad Aulia Fajri; Muhammad Tareq Aziz; Muhammad Arif (Jurnal Ekonomi dan Bisnis, 2024)
Developmental aspirations include achieving high standards of governance. But for this to happen, several requirements must be met, among them accountability and transparency. The degree to which this metric is met can be used to evaluate the effectiveness of financial governance. The purpose of this study is to determine how accountability and transparency affect the standard of financial governance in the North Sumatra Ministry of Religion. Then, conduct in-depth analysis and research to produce clear facts that may be used as study material and to generate ideas about how one variable mayaffect other factors in future research. It is a qualitative method with a literature review approach. Mendeley, Google Scholar, and international journal articles are needed for a literature review in the process of assessing the facts and information needed to examine hypotheses and theories in further detail. This technique of research necessitates the capacity to investigate findings from research journals, earlier scientific work, and contemporary phenomena in order to critique and analyze them. The findings of this study provide an explanation of the beneficial effects of accountability and transparency on the standard of financial governance in the North Sumatra Ministry of Religion. Image, involvement, and completeness of reports are all provided by transparency. Accountability, meantime, determines the publication's accuracy once a year in compliance with governmental regulations. In order to strengthen the value of the organization, both positively affect the standard of financial governance at the North Sumatra Ministry of Religion.